Educação bilingue para surdos: práticas discursivas em tempos de exclusão - Bosco, Daniella Cristina [UNESP] (2014)
Studying bilingual education for the deaf students in different contexts of escolarization implies in an approximation of a complex phenomenon of educational reality and fraught with tensions in which competing forces of different segments of society in an attempt to define the best institutional setting, that bilingual education can tale on within formal education systems. Considering this problem, this research focuses on analyzing the contributions of discursive practices in the constitution of bilingual subjects in two educational spaces: an inclusive school with bilingual proposition and a bilingual school for the deaf. Thus, the theoretical framework for this study comes from the contributions of cultural-historical psychology and Bakhtin’s dialogical principle and addition to the reference works in the field of deafness. To accomplish these objectives were made surveys of discursive practices involving different subjects present in the classroom, in two schools were conducted that adopted the bilingual education philosophy.As investigation procedures data was collected through observations and filming of discursive practices in the classroom. Data were collected from March 2012 to March 2013 and, after collection, the material obtained with filming underwent transcription as proposed in Quadros and Karnopp (2004) and Lodi (2006) studies. The selection of fragments referring to data collected through video recordings and observations of discursive practices occurred by movement back to the epistemological and theoretical assumptions which led to the development of this research.The search for the selection of fragments of enunciation deduced the detailed assessment of enunciation shared between teacher, interpreter, hearing and deaf students (inclusive education) and bilingual teacher and deaf students (bilingual school for the deaf), during the process of production of meanings in the classroom. The focus of this analysis focused...